Simulation Modelling or Production Planning and Control of Boeing Aircraft's Composites Parts - Mohd. Kamal, Mohd. Nawawi (2003)
Simulation is one of the most powerful tools available to decision-makers responsible for the design and operation of complex processes and systems. One of the largest application areas for simulation modelling is that of manufacturing systems. This study is conducted at the manufacturing plant that manufactures composite products to the aerospace industry. In this study, simulation technique is applied to model the existing system and then used to simulate the design and operational policies of the plant production process, which can be used to improve the performance of the different activities at the factory. Among the activities involved in the process are the operations of laminating of plies, curing, cutting, painting, and inspection of parts. The research and the simulation model developed have improved the understanding of the inter-relationship of the several physical components of the plant. The process of constructing the simulation models and reviewing the interaction of these components has given an insight into the different operational characteristics at the plant. The approach of system analysis is not only beneficial to the modeller, but it is also useful to the planner since it gives a thorough understanding how the plant behaves and not how one thinks it behaves.